In the Midst of the COVID-19 Pandemic, Politeknik Negeri Media Kreatif Used Flat Design Techniques as Educational Animation Media Material - Komda Saharja; Suhendra Suhendra (The IJICS (International Journal of Informatics and Computer Science), 2021)
The more innovation creates, the more inventive, seriously intriguing, and more imaginative limited time media, remembering special media for the type of movement illustrations.  Politeknik Negeri Media Kreatif (Polimedia) Medan grounds is the object of exploration. The exploration utilizes a writing concentrate on research strategy, perception of Polimedia, which is a Vocational College as a substance reference. As a professional school, its reverberation isn't apparent at the degree of North Sumatra, a successful limited time media to the local area, particularly amidst the Covid-19 pandemic, Polimedia should focus on instructive media content that is appealing to its partners. The motivation behind this review is to deliver movement illustrations activity video media as instructive liveliness media content with level plan procedures with the objective of secondary school/professional youth who will proceed with their schooling to a more explicit level as indicated by proficient interests. The phases of the exploration strategy incorporate writing study, meetings to discover the means of Polimedia in presenting its grounds and dispersing polls to the plan target. Phases of creation include: pre-creation, creation, and after creation. In light of the exploration in the field, it reasoned that the pre-creation stage is the idea of typography and storyboard plan. At the phase of the creation cycle, to be specific Character Building (Drawing), Modeling, Facility Design, Animation and Post-Production Processes including Altering, audio cues, delivering, dominating, distributing recordings